Irreversible inhibition of rat glutathione S-transferase 1-1 by quinones and their glutathione conjugates. Structure-activity relationship and mechanism. - van Ommen, B (1991)
The irreversible inhibition of the rat glutathione S-transferase (GST) isoenzyme 1-1 by a series of halogenated 1,4-benzoquinones and their GSH conjugates was studied quantitatively by analysing the time course of enzyme inactivation. With increasing numbers of chlorine substituents, the rate of inhibition greatly increased. Incorporation of a GSH moiety in all cases increased the rate of inactivation compared with the non-substituted compound, and this was due to the increased affinity of the inhibitor for the active site. The ratio between the rates of inhibition for a given quinone with and without GSH substituent was largest for the three dichlorobenzoquinones, with the 2,6-isomer showing a 41-fold increase in rate of inhibition upon conjugation with GSH. The time courses of inhibition could be fitted either to a bi-exponential function (for the GSH conjugates and the higher chlorinated quinones) or to a mono-exponential function (all other quinones). It is concluded that the second component describes the affinity part of the reaction. GST 1-1 possesses two cysteine residues, with modification of one of these, probably located in the vicinity of the active site, having a major impact on the enzyme activity. Compounds with affinity towards the active site preferentially react with this residue. Non-specific quinones react equally with both cysteine residues. This was confirmed by the observation that complete inactivation of GST 1-1 by 2,5-dichlorobenzoquinone was achieved only after modification of two residues, whereas the corresponding GSH conjugate already completely inhibited the enzyme after modification of one residue.